2001
DOI: 10.1007/bf03016694
|View full text |Cite
|
Sign up to set email alerts
|

Des diagnostics cliniques et échocardiographiques contradictoires dans des cas d’instabilité hémodynamique inexpliquée à la suite d’une intervention en cardiochirurgie

Abstract: P Pu ur rp po os se e: : To investigate 1) if clinical indications match diagnostic findings from urgent transesophageal echocardiography (TEE) in hemodynamically unstable patients after cardiac surgery and 2) the clinical impact of the TEE findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…There were seven studies reporting the use of transthoracic echocardiography [9,11,[18][19][20][21][22] and eight for transoesophageal echocardiography [23][24][25][26][27][28][29][30]. There were eight uncontrolled prospective observational studies [9, 11, 19, 21-23, 26, 28], and seven retrospective cohort studies [18,20,24,25,27], of which only two had a control group [29,30]. There was considerable variability in the study aims, indications for echocardiography, patient populations and end-points used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were seven studies reporting the use of transthoracic echocardiography [9,11,[18][19][20][21][22] and eight for transoesophageal echocardiography [23][24][25][26][27][28][29][30]. There were eight uncontrolled prospective observational studies [9, 11, 19, 21-23, 26, 28], and seven retrospective cohort studies [18,20,24,25,27], of which only two had a control group [29,30]. There was considerable variability in the study aims, indications for echocardiography, patient populations and end-points used.…”
Section: Resultsmentioning
confidence: 99%
“…Transthoracic echocardiography frequently identified cardiac dysfunction in 36% of patients in whom it was not suspected clinically, even though transthoracic echocardiography was used as a screening tool, rather than for an indication such as haemodynamic instability. There were three studies that reported a change in diagnosis between transoesophageal echocardiography and clinical assessment (25-59%) [25,29,30]. Pericardial effusion was detected with transoesophageal echocardiography more frequently (6-48%) than transthoracic echocardiography (2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing familiarity and certification of CSRU consultants in transesophageal echocardiography could have been helpful in promoting earlier surgical reintervention in hemodynamically unstable patients, given recent evidence of discordance between clinical and echocardiographic diagnoses in patients with unexplained hemodynamic instability after cardiac surgery. 12 Moreover, the change in the consultant call system to a day-night rotation involving two consultants instead of the previous single consultant per week may have had an independent beneficial effect. In addition, an acute care nurse practitioner joined the CSRU team at the beginning of year 2 of the study, whereas no nurse practitioner had worked in the medical-surgical ICU at the receiving institution prior to merger.…”
Section: Discussionmentioning
confidence: 99%
“…30 A recent study also highlighted the utility of TEE in assisting management strategies in 58% of postoperative cardiac surgical patients who had TEE. 31 A secondary finding was a lower associated mortality in patients having a surgical intervention as a result of the TEE diagnosis. Our study differs significantly from this previous study as we examined the role of TTE in predicting mortality in a much larger group of patients admitted to the MSICU.…”
Section: Objectifmentioning
confidence: 99%